Influence of sidestepping expertise and core stability on knee joint loading during change of direction - Duchene, Y.; Gauchard, G. C.; Mornieux, G. (Journal of Sports Sciences, 2022)
The aims of this study were twofold: first, to compare core stability and knee joint loading between sidestepping experts and nonexperts; secondly, to determine core predictors of knee joint loading. Thirteen handball male players (experts) and 14 karatekas (nonexperts) performed six unanticipated 45° sidestepping manoeuvers, while trunk and pelvis 3D kinematics as well as ground reaction forces were measured, and peak knee abduction moment (PKAM) was determined. Student t-tests enabled a comparison of both groups and a linear mixed model approach was used to identify PKAM predictors. Sidestepping experts demonstrated significantly lower pelvis rotation towards the new movement direction at the initial contact than nonexperts (4.9° vs. 10.8°) and higher PKAM (0.539 vs. 0.321 Nm/kg-bwt). Trunk medial lean, trunk axial rotation and pelvis anterior tilt at the initial contact predicted PKAM, while trunk axial rotation, pelvis medial lean and posterior ground reaction force predicted PKAM during the weight acceptance phase. Despite higher PKAM, handball players might not be at a higher risk of anterior cruciate ligament injury as the knee joint loading remained at a relatively low level during this sidestepping task. Core stability, in its three dimensions, is a key determinant of knee joint loading.